Pelatihan Pembuatan E-Commerce dan Promosi Melalui Tokopedia pada UMKM Siengkong Tapiok Bogor - Suminten Suminten; Saridawati Saridawati; Bisri Bisri; Mohammad Aris (BADAN PENERBIT STIEPARI PRESS, 2024)
This community service is in collaboration with MSME partner Siengkong TapiOk Bogor. This MSME is a food business that carries an urban and sustainability theme that focuses on local Indonesian food. This business is local Indonesian food with unique and modern flavors. For this reason, Siengkong TapiOk was made a partner in this PM so that partners can become facilitators in guiding local residents to be more productive and creative to meet the economic stability of the people of Bogor. Based on the results of the situation analysis, we discussed material that could at least help overcome the existing problems. The PM theme is